A New Tetradentate Mixed Aza-Thioether Macrocycle and Its Complexation Behavior towards Fe(II), Ni(II) and Cu(II) Ions - Sze-Wing Ng; Siu-Chung Chan; Chi-Fung Yeung; Shek-Man Yiu; Chun-Yuen Wong (Molecules, 2020)
A new tetradentate mixed aza-thioether macrocyclic ligand 2,6-dithia[7](2,9)-1,10-phenanthrolinophane ([13]ane(phenN2)S2) was successfully synthesized. Reacting metal precursors [Fe(CH3CN)2(OTf)2], Ni(ClO4)2·6H2O, and Cu(ClO4)2·6H2O with one equivalent of [13]ane(phenN2)S2 afforded [Fe([13]ane(phenN2)S2)(OTf)2] (1), [Ni([13]ane(phenN2)S2)](ClO4)2 (2(ClO4)2), and [Cu([13]ane(phenN2)S2)(OH2)](ClO4)2 (3(ClO4)2), respectively. The structures of [13]ane(phenN2)S2 and all of its metal complexes were investigated by X-ray crystallography. The [13]ane(phenN2)S2 was found to behave as a tetradentate ligand via its donor atoms N and S.